The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/ndt.s220743
|View full text |Cite
|
Sign up to set email alerts
|

<p>Disrupted Brain Entropy And Functional Connectivity Patterns Of Thalamic Subregions In Major Depressive Disorder</p>

Abstract: PurposeEntropy analysis of resting-state functional magnetic resonance imaging (R-fMRI) has recently been adopted to characterize brain temporal dynamics in some neuropsychological or psychiatric diseases. Thalamus-related dysfunction might be a potential trait marker of major depressive disorder (MDD), but the abnormal changes in the thalamus based on R-fMRI are still unclear from the perspective of brain temporal dynamics. The aim of this study was to identify local entropy changes and subregional connectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
4
8
0
Order By: Relevance
“…Thus, this heterogeneity may explain the differences in the results across thalamic subregions. The findings of heterogeneity across thalamic subregions were indirectly supported by the results of our previous study [ 6 ], which, through functional imaging data, revealed that MDD patients exhibited distinct resting-state functional connectivity patterns across thalamic subregions.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Thus, this heterogeneity may explain the differences in the results across thalamic subregions. The findings of heterogeneity across thalamic subregions were indirectly supported by the results of our previous study [ 6 ], which, through functional imaging data, revealed that MDD patients exhibited distinct resting-state functional connectivity patterns across thalamic subregions.…”
Section: Discussionsupporting
confidence: 80%
“…Nor does it mean that other functional MRI data of the thalamus are not suitable to be chosen as features for individualized recognition of MDD patients. One of our previous studies showed sample entropy changes in the bilateral thalami in MDD patients [ 6 ], so we are considering using the sample entropy of the resting-state fMRI data as a feature for the classification and prediction of MDD in our future studies [ 4 ]. The whole brain volume was not controlled as a covariate in this study, which may have potential correlation with the volume of the thalamus, and could be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amygdala [26,36] (part of the subcallosal region), regions in the inferior temporal [56], the medial frontal lobe [56], posterior cingulate cortex [63] and supplementary motor area [64] have been implicated in MDD. In [61], disruption between the connections between regions in the thalamus and the transverse temporal gyrus were reported, which our consistent with our results.…”
Section: Identified Salient Features Are Clinically Relevantsupporting
confidence: 93%